PENGARUH PROFITABILITAS DAN SOLVABILITAS TERHADAP HARGA SAHAM PADA PT GUDANG GARAM TBK TAHUN 2012-2022 - Ashwin Sani; Nani Rusnaeni (Journal of Research and Publication Innovation, 2025)
This research aims to determine whether there is a significant influence between Profitability (ROA) and Solvency (DAR) on share prices. The method used in this research is a quantitative method in retrieving Financial Report data from PT Gudang Garam, Tbk for the 2012 – 2022 period. Data analysis uses descriptive statistical analysis, classical assumption testing, simple linear regression analysis, multiple linear regression analysis, hypothesis testing, and coefficient of determination. The results of this research partially show that the Profitability variable as measured by Return On Assets (ROA) has a significant effect on stock prices, and Solvency as measured by the Debt to Asset Ratio (DAR) does not have a significant effect on stock prices. Simultaneously, Return on Assets (ROA) and Debt To Asset Ratio (DAR) have an influence on share prices. where Fcount 5.300 > Ftable 4.459 with a significance level of 0.034 < 0.05.